Determinação do grau de hidratação da níquel – fluorohectorita por difração de raios x oriundos de fonte de luz síncrotron - Oliveira, Jeane Silveira de (2013)
Clays are major constituent of the soil and due to its properties (plasticity, malleability, and affinity for water and adhesion to certain surfaces) they are widely used in industry and research. The particles are formed in a stacked structure due the interlayer cations. The fluorhectorite is 2:1 clay chemically synthesized. It has platelets structure with the size ranging from 20 nm to 10 μm, in the case of Nickel-fluorhectorite (Ni-FH) the interlayercation is Nickel. According to the literature, the properties of fluorohectorite are strongly dependent on the interlayer cation. Many studies have been conducted with sodium-fluorhectorite (Na-FH), but little is known about the Ni-FH, before it proposed a study of the behavior of clay in a range the closer environmental temperature. X-ray diffraction, performed in a synchrotron facility, was conducted in order to study the hydration regimes of Ni-FH. The experiment consists in a temperature variation, with precise intervals of 1°C, without moisture control of atmospheric pressure on the sample. The diffraction patterns were treated with background subtraction and the peaks were adjusted with a pseudo-Voigt function in order to obtain the experimental parameters. The peak positions were used to calculate the basal spacing of the clay at each temperature. The results show that in the region of 14 °C to 32 °C, the Ni-hydrated FH has two hydration states, 1 and 2 water layers (WL), with an increase of approximately 2 Å in basal spacing. The analysis was consisted in two parts: the peak position and width at half maximum (FWHM). From the former it was showed that the water intercalation process is more dependent on the relative humidity than the temperature variation. And from the latter it was showed that the crystallite size of the clay increases as the relative humidity rises. The study exposes a need for more experiments at higher temperature range in order to reach other hydration states. The results, when compared to the well-known Na-FH, shows that although the interlayer cation is different both clays have some similarities.